A Measure of value-at-risk (VaR) for fat-tailed distributed Philippine stock index and Philippine portfolios with selected international stock indices an Extreme Value Theory (EVT) - Copula approach - Quismorio, Brenda A.
Financial crises have shown the importance of having an accurate risk measurement that takes into account extreme losses. These crises reveal that risk management tools based on the averages and variances are inadequate in considering extreme losses. In addition, the traditional measure of the comovement of returns called.